Analysis Of Tourism Object Development Strategie Mari Pro Sembahe Deli Serdang - Arihta Rido Alfrendo Sembiring; Edi Winata (Jurnal Ekonomi, 2024)
This research aims to conduct an analysis of the strengths, weaknessesopportunities and threats in strategic efforts to develop the Mari Pro tourist attraction in Hamlet 2, Tambunan Village, Sibolangit District, Deli Serdang Regency. Then the application in carrying out development is analyzed by minimizing weaknesses and threats, optimizing the use of opportunities and strengths. Data was collected through literature study, observation and also interviews with informants, local communities and visitors. The data was analyzed in a descriptive manner, then analysis of the implementation of the strategy for developing Mari Pro tourist attractions was carried out through SWOT analysis. Based on the research results, it can be concluded that the strategy analysis in developing the Mari Pro Sembahe tourist attraction is optimizing the program by utilizing the potential of the Mari Pro Sembahe tourist attraction, utilizing communication and tel ecommunications technology in an effort to maximize promotion, improving the management of tourist attractions, improving facilities. as well as access to tourist attractions so that the analysis of Mari Pro's tourist attraction development strategy is getting better.